Penegakan Hukum terhadap Pekerja Imigran China di Indonesia Selama PPKM dan PSBB - Zermiyaz, Muhammad Firly; Pambudi, Triantomo; Dyantara, Ihsanutama Arya Prima (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The COVID-19 pandemic has greatly affected the Indonesian economy, especially the welfare of Indonesian workers. During this pandemic, there are still violations of the law on immigrant or foreign workers. This study aims to discuss how the conditions that occur during the arrival of Chinese work migrants and how the rules or policies regulate this. The method used in this study is a qualitative approach with data collection using literature studies. Based on research results from literature studies, the government claimed to have brought workers from China into Indonesia. This action is of course very contrary to what is happening and the government's efforts so far to suppress the number of COVID-19. Even though the unemployment rate is increasing due to layoffs such as the number of 1,722,958 people, the government still allows foreign workers from China to enter and seems to prevent local Indonesian workers from working. In fact, in Government Regulation Number 34 of 2021 as the central legal basis, permits for extension of workers and strict selection of workers must still be carried out consistently. In conclusion, the immigration and labor sector in Indonesia still shows clear shortcomings.